Peningkatan Proses dan Hasil Belajar pada Mata Pelajaran Matematika Menggunakan Model Numbered Head Together di Kelas V SDN 97/II Muara Bungo - Fitra Darmawansyah; Randi Eka Putra; Aldino Aldino (CV. Master Literasi Indonesia, 2025)
The motivation for this study arose from the unsatisfactory mathematics learning processes and achievement levels of fifth-grade students at SDN 97/II Muara Bungo. The problem was evident from students’ limited involvement in learning activities and the average final exam scores below the Minimum Mastery Criteria (KKTP) of 70. The research employed Classroom Action Research (CAR) conducted in two cycles with 24 students as subjects. Data were collected through observation and tests using observation sheets and evaluation questions. The results indicated that the application of the Numbered Head Together (NHT) model improved both the learning process and outcomes. Teacher performance increased from 80% in cycle I to 90% in cycle II, while student engagement rose from 45.83% to 83.33%. Student achievement also improved from 45.83% in cycle I to 83.33% in cycle II. Therefore, NHT proved effective in enhancing mathematics learning quality in elementary schools